BRIGDES BETWEEN CULTURES: RUSSIAN AND SERBIAN VISUAL ARTS TERMS - D.I. Medvedeva; L.N. Lisitsyna (Многоязычие в образовательном пространстве)
The paper is devoted to the comparative analysis of visual art terms in Russian and Serbian languages. The relevance of the study is conditioned by the developing cooperation between Russian and Serbian artists and art institutions. The research is based on more than 140 terms taken from bilingual dictionaries and art-focused sites. The methods employed are: comparative analysis, semantic analysis, and etymologic analysis. The study of the material allows us to establish the fact that the majority of terms in both Russian and Serbian are borrowed from French, Italian, German, and English, whereby French dominates as the source language. The Serbian language has been strongly influenced by the German, both as a source language and as a mediator language in the course of borrowing the French terms. Moreover, Serbian proves to be more inclined to loan translations of visual art terms. As for the terms concerning artists and their activities, the Russian language is characterised by the tendency towards generalisation and polysemy, and the Serbian language is marked by a tendency towards generalisation.